2018
DOI: 10.18632/oncotarget.26443
|View full text |Cite
|
Sign up to set email alerts
|

NEO412: A temozolomide analog with transdermal activity in melanoma in vitro and in vivo

Abstract: Despite new treatments introduced over the past several years, metastatic melanoma remains difficult to cure. Although melanoma in situ (MIS) has better prognosis, it relies heavily on thorough surgical excision, where ill-defined margins can pose a challenge to successful removal, potentially leading to invasive melanoma. As well, MIS in the head and neck area can create serious aesthetic concerns with regard to the surgical defect and substantial scar formation. Toward improved treatment of localized melanom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…In a mouse model of subcutaneous melanoma, topical application of NEO412 increased tumor cell death, along with decreased neo-angiogenesis in tumor tissue. Intriguingly, these effects could also be observed in tumors that were located distant from the skin treatment site, indicating that topical NEO412 was able to enter the circulation and reach tumor cells that might have metastasized already [201]. Although it remains to be established how much each penetration enhancer, i.e., POH vs. linoleic acid, contributed to transdermal migration of the tripartite molecule, the significant anti-melanoma effect that was achieved clearly indicates the benefit of this combination.…”
Section: Poh and Penetration Of The Skinmentioning
confidence: 97%
See 1 more Smart Citation
“…In a mouse model of subcutaneous melanoma, topical application of NEO412 increased tumor cell death, along with decreased neo-angiogenesis in tumor tissue. Intriguingly, these effects could also be observed in tumors that were located distant from the skin treatment site, indicating that topical NEO412 was able to enter the circulation and reach tumor cells that might have metastasized already [201]. Although it remains to be established how much each penetration enhancer, i.e., POH vs. linoleic acid, contributed to transdermal migration of the tripartite molecule, the significant anti-melanoma effect that was achieved clearly indicates the benefit of this combination.…”
Section: Poh and Penetration Of The Skinmentioning
confidence: 97%
“…NEO412 is a tripartite agent consisting of three bioactive agents: POH, TMZ, and linoleic acid, with the latter representing a well-established transdermal penetration enhancer [199,200]. In vitro studies confirmed that NEO412 was able to effectively kill melanoma cells through the alkylation effect of TMZ [201]. In a mouse model of subcutaneous melanoma, topical application of NEO412 increased tumor cell death, along with decreased neo-angiogenesis in tumor tissue.…”
Section: Poh and Penetration Of The Skinmentioning
confidence: 99%
“…This effect included a combination of increased tumor cell death with only minor blood vessel development. Drug-treated mice exhibited no apparent damage relative to healthy skin in response to periodic drug application [ 48 ].…”
Section: Perillyl Alcohol and Its Derivativesmentioning
confidence: 99%
“…with only minor blood vessel development. Drug-treated mice exhibited no apparent damage relative to healthy skin in response to periodic drug application [48]. Two novel amide derivatives 24 and 25 of (S)-perillic acid (Figure 12) were designed and synthesized.…”
Section: Perillyl Alcohol and Its Derivativesmentioning
confidence: 99%
See 1 more Smart Citation